Effect of Morinda citrifolia leaf as saponin sources on fermentation characteristic, protozoa defaunated, gas and methane production of ruminal fluid in vitro - Hendra Herdian; L. Istiqomah; A. Febrisiantosa; D. Setiabudi (Indonesian Center for Animal Research and Development (ICARD), 2011)
Many studies have reported that the Morinda citrifolia (pace plant) was a useful material for human health. However the exploration of this plant on rumen fermentation is still needed. Therefore, a research was done to study the effect of M. citrifolia leaf on fermentation characteristics of rumen fluid consisted of protozoa defaunated process, VFA composition, NH3 content, rumen microbial protein content, gas and methane production using in vitro techniques. Rumen fluid obtained from two fistulated Ongole crossbreed cattle fed with forage and concentrate feed ration (70 : 30). The fluid was incubated at 39ºC for 48 hours. The treatment on the rumen fluid consisted of control treatment: 100% (200 mg DM) kolonjono forage substrate (Penisetum purpureum) and M. citrifolia treatments: kolonjono forage plus M. citrifolia (equivalent saponin) 3; 6; 9; and 12 mg DM, respectively. The treatment of M. citrifolia leaf addition showed declined patterns in the number of protozoa population (P < 0.05) compared to control. There was no effect of M. citrifolia treatment on VFA composition and NH3 content (P > 0.05). Microbial protein content in rumen fluid increased (P < 0.05) by M. citrifolia treatments compared to control. Effect of M. citrifolia treatments on the gas production was not significantly different (P > 0.05) compared to control, while M. citrifolia treatments reduced the methane gas production of (P < 0.05) compared to control. It was concluded that M. citrifolia leaf has potential as a limiting agent of protozoa population and methane gas production in rumen. Key words: M. citrifolia, Defaunated, Saponin, In Vitro